Bioinformatics-based analysis of the relationship between STC1 expression and immune infiltration in gastric cancer - Ma, Weijun; Ma, Xiaoli; Li, Yaoqi (Frontiers in Genetics, 2025)
ObjectiveThe study assessed the expression of STC1, and its potential as an immunotherapy target in gastric cancer (GC).MethodsRNAseq data from the TCGA_STAD project and TCGA-GTEx project of UCSC XENA website and microarray data from GEO (GSE66229) were downloaded. Differential STC1 mRNA expression between GC and non-carcinoma tissues was examined. Its relation to clinicopathological characteristics and prognosis was evaluated using univariate and multivariate Cox regression. Tumor infiltrating immune cells (TIICs) in the tumor microenvironment (TME) were assessed by ssGSEA, and T-cell exhaustion by TIMER. Single-cell RNA sequencing (scRNA-seq) analysis was performed to validate the correlation between STC1 expression and T-cell exhaustion markers. Gene Set Enrichment Analysis (GSEA) was also conducted to explore potential functions of STC1 in GC.ResultsSTC1 expression was significantly higher in GC tissues and independently predicted poor overall survival. STC1 expression was related to patient T-stage, location, and overall survival events. Immune infiltration analysis showed significant associations between STC1 and multiple immune cells in TME, with strong links to T-cell exhaustion. scRNA-seq analysis confirmed the co-expression of STC1 with T-cell exhaustion markers in specific cell clusters. GSEA identified several signaling pathways, such as “SIGNALING_BY_INTERLEUKINS” and “JAK_STAT_SIGNALING_PATHWAY,” linked to STC1 expression in GC.ConclusionSTC1 is a promising target for immunotherapy in GC, as its expression is correlated with patient prognosis, immune infiltration, and T-cell exhaustion.